2020
DOI: 10.1177/0022146520945047
|View full text |Cite
|
Sign up to set email alerts
|

Organized Labor and Depression in Europe: Making Power Explicit in the Political Economy of Health

Abstract: Despite engagement with the construct of power relations, research on the political economy of health has largely overlooked organized labor as a determinant of well-being. Grounded in the theory of power resources, our study aims to fill this gap by investigating the link between country-level union density and mental health while accounting for the compositional effects of individual-level union membership. We use three waves of the European Social Survey (N = 52,737) and a variation on traditional random-ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…One can think of a few plausible pathways. On one hand, polarization can be seen as an indicator of a less regulated labour market that does not prevent the creation of precarious, poorly paid, and stressful jobs, and probably makes it difficult for people with unsatisfactory working conditions to leave their jobs, at the risk of their own health [ 38 ]. On the other hand, the rise of top market incomes also reflects the political weight of the rich, who are less likely to favour universal, generous, and healthy social programs [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…One can think of a few plausible pathways. On one hand, polarization can be seen as an indicator of a less regulated labour market that does not prevent the creation of precarious, poorly paid, and stressful jobs, and probably makes it difficult for people with unsatisfactory working conditions to leave their jobs, at the risk of their own health [ 38 ]. On the other hand, the rise of top market incomes also reflects the political weight of the rich, who are less likely to favour universal, generous, and healthy social programs [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…They encourage researchers to examine these concepts as forces influencing work, safety, health, and well-being. Despite these repeated calls for addressing power in occupational health research, empirical studies that directly investigate power remain scarce [ 62 , 63 ]. In the next section, we describe approaches to incorporate the concept of power in EQ research.…”
Section: Recognizing Power and Its Social Configuration As It Relates...mentioning
confidence: 99%
“…Collective bargaining is associated with improved population health-but does it affect everyone's health in the same way? The share of the population that belongs to a union (union density) is associated with lower mortality in the population (Muntaner et al, 2002), better self-reported health (Dollard and Neser, 2013) and lower depression amongst the workforce, even for those who are not unionized (Reynolds and Buffel, 2020). Reeves (2021) shows that collective bargaining institutions reduce mortality and raise life expectancy at the country level.…”
Section: Dualization Collective Bargaining and Healthmentioning
confidence: 99%